2020
DOI: 10.1186/s12998-020-00346-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing forces during spinal manipulation and mobilization: factors influencing the difference between forces at the patient-table and clinician-patient interfaces

Abstract: Background Spinal manipulative therapy (SMT) and mobilization (MOB) effects are believed to be related to their force characteristics. Most previous studies have either measured the force at the patient-table interface or at the clinician-patient interface. The objectives of this study were to determine 1) the difference between the force measured at the patient-table interface and the force applied at the clinician-patient interface during thoracic SMT and MOB, and 2) the influence of the SMT/MOB characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 32 publications
1
23
4
Order By: Relevance
“…The STAI-YB or Trait questionnaire evaluates general states of calmness, confidence, and security. A total score of the YA and YB questionnaires gives a rate of anxiety that can be classified as very low (0-35), low (36)(37)(38)(39)(40)(41)(42)(43)(44)(45) moderate (46)(47)(48)(49)(50)(51)(52)(53)(54)(55), high (56-65), and severe (>65) for each questionnaire (30,31). Finally, the level of comfort during SMT was assessed following the intervention, using a 100-mm scale, a higher score indicating a very comfortable procedure and a lower score a very uncomfortable one.…”
Section: Candidate Prognostic Factorsmentioning
confidence: 99%
“…The STAI-YB or Trait questionnaire evaluates general states of calmness, confidence, and security. A total score of the YA and YB questionnaires gives a rate of anxiety that can be classified as very low (0-35), low (36)(37)(38)(39)(40)(41)(42)(43)(44)(45) moderate (46)(47)(48)(49)(50)(51)(52)(53)(54)(55), high (56-65), and severe (>65) for each questionnaire (30,31). Finally, the level of comfort during SMT was assessed following the intervention, using a 100-mm scale, a higher score indicating a very comfortable procedure and a lower score a very uncomfortable one.…”
Section: Candidate Prognostic Factorsmentioning
confidence: 99%
“…The literature search was updated on June 30, 2021, and led to the identification of three additional articles fulfilling the inclusion criteria. Forty-six studies were deemed relevant and were included in this review ( 7 12 , 15 54 ). The literature search also revealed seven literature reviews from which no additional original studies were identified ( 2 , 6 , 55 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, pooling measures recorded by different devices might not be appropriate. Specifically, it has been shown that forces with specific characteristics measured at the clinician-patient interface present different characteristics than the ones measured simultaneously at the patient-table interface ( 15 ). Additionally, even though different devices might measure force-time characteristics in a similar manner (i.e., at the same interface), each device has its specific metrologic properties (e.g., reliability, validity, specificity, and sensitivity), which influence the confidence in the measured values.…”
Section: Introductionmentioning
confidence: 99%
“…General age-related degenerative changes have been reported in the literature (Sharma and Goodwin, 2006), as well as its influence on the biomechanics of the ribs and the overall thoracic region (Agnew et al, 2015;Brown et al, 2008;Forman et al, 2015;Kang et al, 2020;Okada et al, 2019). Apart from thoracic biomechanical behaviour, intervention and participant characteristics have been observed to influence the difference between forces measured at the clinician-participant and participant-table interfaces: where lower SMT loading rates (intervention) and larger thoracic thickness (participant) were correlated with a smaller difference between forces at both interfaces (Mikhail et al, 2020). Therefore, it can be speculated that the degenerative changes occurring in older adults, in combination with the intervention and other participant specific characteristics may influence the forces acting on internal tissues during MOB and SMT, which seems to be distinct from the ones observed in younger adults.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study in asymptomatic young participants (mean age: 24 years old ±2.7) measured SMT force-time characteristics at the clinician-participant and participant-table interfaces and observed that forces at the participant-table interface were greater than the ones at the clinician-participant interface during MOB and SMT in most participants (Mikhail et al, 2020). Similar findings were observed in a recent study conducted in our lab where forces at the participant-table were, on average, 14% larger than forces at the clinician-participant interface (unpublished data).…”
Section: Discussionmentioning
confidence: 99%